Cytopathogenicity studied of fowl pox virus by using indirect immunoperoxidase and acridine orange tests .: Harith M. AL-Hyali , Aied B. AL-Zughaibi and Suad Abdulkarim. - AL-Hyali, Harith M. (The Iraqi Journal of Veterinary Medicine, 2005)
Locally isolated fowl pox virus was inoculated on chorioallantoic membraneof chick embryos, leads to the appearances of odema and pocks lesion on themembrane , 120 hours post inoculation .Virus assay showed that the infectivitytiter were 106.8 to 107.5 EID50/0.1 ml in embryonated chicken eggs. Monolayertissue cultures of chick embryo fibroblast cells infected with fowl pox virus wereexamined by acridine orange staining and indirect immunoperoxidase test to studythe cytopathogenic effects of the virus . The most striking cytoplasmic changesobserved was the presence of the intracytoplasmic inclusions at 24-48 hours postinoculation, numerous inclusions were clearly seen at 72 hr. P.I.in addition tocytoplasmic vaculation and granulation were clearly seen at 96 hr. P.I. Thesechanges stained brilliant green with acridine orange and dark brown staining withimmunoperoxidase . Both tests demonstrated the localization of pox virus antigensin infected cells at same intervals.